Las bibliotecas como elementos para el desarrollo - Fuentes Romero, Juan José (Revista General de Información y Documentación, 2007)
Libraries are today considered as essential elements about development. We study the caracteristics of less developed countries, the actual meaning of the word development», the diverse considerations of some academics on the relationship between libraries and development and, as well, the question of publishing and reading in the so called «less developed countries». After the analysis of the actuation of international organizations as UNESCO and IFLA, we stablish some general conclusions about libraries and development.
Keywords: Libraries; Development; Less developed countries